Reye syndrome and liver transplantation - Cağ, Murat; Saouli, Anne-Catherine; Audet, Maxime; Wolf, Philippe; Cinqualbre, Jacques (The Turkish Journal of Pediatrics, 2010)
Reye syndrome is a rare, but severe and often fatal disease. The etiology of the classical Reye syndrome is unknown, but it is typically preceded by a viral infection with a free interval of three to five days. The main physiopathological hypothesis is a mitochondrial metabolism insult causing acute liver failure and encephalopathy. Survivors present serious neurological sequelae. The treatment of Reye syndrome is usually medical with intensive care management. Herein, we present the clinical case of a six-month-old baby diagnosed with Reye syndrome with a fulminant hepatitis, who was successfully liver transplanted with an auxiliary partial orthotopic liver transplantation.